?pm-Statistical Convergence of Order ? - Karakas, Abdulkadir; Altin, Yavuz; Et, Mikail (Amer Inst Physics, 2017)
In this study using the generalized difference operator Delta(m), we generalize the concepts of statistical convergence sequences of order a and statistical Cauchy sequences of order alpha. It is shown that, Delta(m)(p)-statistically convergent sequences of order a and Delta(m)(p)-statistical Cauchy sequences of order a are equivalent.
2nd International Conference on Advances in Natural and Applied Sciences (ICANAS) -- APR 18-21, 2017 -- Antalya, TURKEY
Keywords: Lacunary Statistical Convergence; Sequences; Spaces; Sets